Inflammatory dentigerous cyst following unresolved endodontic infection of deciduous teeth: A report of three cases with CBCT imaging. Issue 1 (April 2022) - Shujaat, Sohaib; Tijskens, Elisabeth; De Grauwe, Annelore; EzEldeen, Mostafa; Jacobs, Reinhilde
Abstract: The inflammatory dentigerous cyst (IDC) occurs as a result of spread of an inflammatory exudate from a non-vital, decayed or endodontically treated deciduous tooth to the permanent tooth follicle. Although diagnosis of the lesion is possible with two-dimensional imaging modalities, nevertheless, three-dimensional (3D) imaging such as cone-beam-CT (CBCT) offers an advantage of assessing the 3D anatomical localization and extension of the cyst, which is necessary for formulating an optimal surgical treatment plan. Due to the rarity of evidence related to CBCT based diagnosis of the IDC, the aim of this study is to present a series of three cases of IDC following endodontic treatment of deciduous molars. A clinician should be aware of the IDC occurrence and perform a regular clinical and radiological follow-up following endodontic interventions and if delayed shedding of the deciduous teeth and dentigerous cyst are observed in the same region. Highlights: Regular follow-up is required for delayed shedding of deciduous teeth and dentigerous cyst occurrence in the same region. Dentists should be aware of the possible spread of inflammation to the underlying tooth follicle. CBCT is helpful for diagnostics, treatment planning and follow-up of the healing process. Treatment options include decompression, marsupialization and/or cyst enucleation, preceded by deciduous tooth extraction. Permanent successors generally do not need extraction and can erupt either spontaneously or with orthodontic therapy.